KETERAMPILAN DIPLOMASI SISWA SMU DI MALANG UNTUK MENAMBAH WAWASAN HUBUNGAN INTERNASONAL - Sulismadi Sulismadi; Gonda Yumitro; Tonny Dian Effendi (Publisher UPT P2M Politeknik Negeri Malang, 2015)
This paper is the result of collaboration program conducted by University of Muhammadiyah Malang and two Senior High Schools in Malang, SMU Arrohmah and SMU Muhammadiyah 1. The activities were in the form of trainings by maintaining the students diplomatic knowledge and skill which named by The Diplomatic Club Program (DCP). This program is important because on everage the diplomatic skill of senior high school students in Malang has not reached the ideal position, though it is very important for the future of Indonesian interests in facing global world development. By this program, it increased the awarness, motivation, and skill of the students towards the diplomacy and inspired them to study more about Indonesian position in international worlds. Simply, in long period this program will benefit a lot to provide well trained and educated agents for Indonesian foreign policy.